2000
DOI: 10.1083/jcb.151.3.507
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Segregation of Sphingomyelin and Cholesterol during Formation of Copi-Coated Vesicles

Abstract: In higher eukaryotes, phospholipid and cholesterol synthesis occurs mainly in the endoplasmic reticulum, whereas sphingomyelin and higher glycosphingolipids are synthesized in the Golgi apparatus. Lipids like cholesterol and sphingomyelin are gradually enriched along the secretory pathway, with their highest concentration at the plasma membrane. How a cell succeeds in maintaining organelle-specific lipid compositions, despite a steady flow of incoming and outgoing transport carriers along the secretory pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 211 publications
(171 citation statements)
references
References 84 publications
(109 reference statements)
8
161
1
1
Order By: Relevance
“…Vesicular transport processes do not seem to play a major role in intracellular cholesterol transport (57)(58)(59). This is in agreement with the recent observation that cholesterol segregates from COPI-coated vesicles during budding from Golgi membranes (36). Current candidates for mediating intracellular cholesterol transport include caveolin (26), possibly in a complex with other proteins (60).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Vesicular transport processes do not seem to play a major role in intracellular cholesterol transport (57)(58)(59). This is in agreement with the recent observation that cholesterol segregates from COPI-coated vesicles during budding from Golgi membranes (36). Current candidates for mediating intracellular cholesterol transport include caveolin (26), possibly in a complex with other proteins (60).…”
Section: Discussionsupporting
confidence: 75%
“…Microdomains have also been suggested to occur as a result of the cholesterol and sphingomyelin gradient along the secretory pathway to explain protein sorting at the Golgi complex (3). Recently, it was found that cholesterol and sphingomyelin are segregated from Golgi-derived COPI-coated vesicles, implicating a segregation process that might involve microdomains within the Golgi complex (36). By detergent extraction, Golgi-derived detergent-soluble complexes (GIC mi- 2, 7, and 8) or presence of 2 mM M␤CD (lanes 3 and 4) or 2 mM M␤CD⅐Chol (4:1) for 2 h at 30°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functioning and processing of membrane proteins critically depend on the way their transmembrane segments are embedded in the membrane 1 Lipidomics of Golgi-derived COPI vesicles unravelled a partial segregation of cholesterol and most SM species except for one (N-stearoyl SM) from the vesicle fraction 5 . In order to understand the molecular mechanisms of SM 18 enrichment in vesicles, we investigated in vivo binding of lipids to p24 and p23, membrane proteins involved in COPI vesicle biogenesis ( Supplementary Fig.…”
mentioning
confidence: 99%